التغيير التنظيمي ودوره في تحقيق متطلبات النجاح الاستراتيجي دراسة تحليلية لاراء عينة من الموظفين في مركز البحث والتطوير في مدينة دهوك - موسى, كسرا عنتر عبدا هلل (Sulaimani Journal for Humanities, 2021)
In the eyes of all organizations, change has become a necessary process to ensure their survival and interaction in an environment dominated by competition, development and continuous modernization, and their continuity and success in this environment is linked to the extent of their readiness and speed in interaction with the internal and external environment and the extent of their adaptation to economic, political and social developments, so the change has an impact. Big in the future of organizations. And the need for these organizations to climb the ladder of strategic success. Therefore, we aim through this research to identify the role of organizational change in its dimensions in achieving the requirements for strategic success in the Research and Development Center in Duhok. The research also assumes the existence of a correlation and impact relationship with statistical significance between the organizational change variable and the strategic success requirements in the researched center. It was tested using a questionnaire form, as a means of collecting data, which was distributed to a sample of employees at the researched center, where (50) forms were distributed and (40) valid forms were retrieved for analysis. For data analysis, the SPSS Version 23 program was used, through which the frequencies, percentages, arithmetic mean and standard deviation were obtained for use in describing and analyzing research variables and their diagnosis. The effect of the independent variable on the dependent variable The research reached a set of conclusions, the most important of which are: 1- There is a strong correlation between organizational change and the requirements for strategic success in the researched center. 2- The existence of an influence relationship with statistical significance between organizational change and the requirements for strategic success in the researched center. The research concluded with a set of proposals for the researched center, the most important of which is the need for the center to continue to make changes to the tools and arts used in performance, in order to reach the high levels of performance required by it, and thus achieve strategic success.
Keywords: Change; Change management; Survival; research and development center; strategic success; Duhok city